Educational Workshop Berbasis HOTS: Upaya Meningkatkan Kualitas Guru SMP dan SMA pada Olimpiade Guru Nasional - Fernandes, Adji Achmad Rinaldo; Lusia, Dwi Ayu; Nisa, Hilwin; Hidayatulloh, Moh Zhafran; Rizqia, Anggun Fadhila; Nasywa, Alfiyah Hanun; Putri, Nazwa Anindya; Amirullah, Khoirul Insan (Seminar Nasional Penelitian dan Pengabdian Kepada Masyarakat 2025, 2025)
The National Teacher Olympiad (OGN) is a prestigious event that aims to improve teacher competence, especially in the field of mathematics, through mastery of pedagogy, learning innovation, and the application of Higher Order Thinking Skills (HOTS). However, junior and senior high school teachers in Malang Regency still face obstacles in the form of limited access to training, lack of professional community, and low literacy in learning technology. This service program was carried out at PP & SMA Sumber Putih, Malang Regency, with the aim of strengthening teacher competence through strategies to strengthen positive mindsets, increase motivation, and interactive training based on Higher Order Thinking Skills. The implementation method includes educational workshops, motivational sessions, group discussions, preparation of learning modules, and reflection to measure the effectiveness of the program. The results of the activity showed an increase in teachers' mental readiness in facing the National Teachers' Olympiad, strengthening the understanding of Higher Order Thinking Skills in mathematics learning, and improving technological skills in the learning process. In addition, training modules are arranged as outputs that can be used continuously. This program contributes to improving the professionalism of teachers, encouraging participation in OGN, and building an innovative and competitive education ecosystem in Malang Regency.